2014
DOI: 10.1186/s13019-014-0177-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between older age and outcome after cardiac surgery: a population-based cohort study

Abstract: ObjectiveOctogenarians (aged ≥ 80 years) are increasingly being referred for cardiac surgery. We aimed to describe the morbidity, mortality, and health services utilization of octogenarians undergoing elective cardiac surgery.MethodsRetrospective population-based cohort study of adult patients receiving elective cardiac surgery between January 1 2004 and December 31 2009. Primary exposure was age ≥80 years. Outcomes were 30-day, 1- and 5-year mortality, post-operative complications, and ICU/hospital lengths of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 19 publications
5
51
1
1
Order By: Relevance
“…Although elderly patients have worse early outcomes compared to younger patients, long-term outcomes for octogenarians at our institution after CABG are similar to, if not better than, the age-adjusted Canadian population. These are demonstrated by previously published reports on our cohort examining intermediate and long-term survival post-operatively for octogenarians compared to younger subjects [ 4 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 75%
“…Although elderly patients have worse early outcomes compared to younger patients, long-term outcomes for octogenarians at our institution after CABG are similar to, if not better than, the age-adjusted Canadian population. These are demonstrated by previously published reports on our cohort examining intermediate and long-term survival post-operatively for octogenarians compared to younger subjects [ 4 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, mitral valve surgery remains controversial in terms of use in octogenarians on grounds of high early mortality and poor long-term survival [ 6 9 ]. Various studies at high-volume cardiac centers reported in-hospital and 30-day mortality up to 25% in octogenarians after mitral valve surgery [ 2 , 8 , 10 , 11 ]. One- and five-year survival rates after mitral valve replacement were reported as 67–56% and 45–29% versus 71–69% and 59–23% after mitral valve repair [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Соответственно, средняя выживаемость составила 14,7 лет в возрастной группе 60-69 лет, 10,7 лет -в возрасте 70-74 года, 8,9 лет -в возрасте 75-79 лет и 7,2 года -у больных >80 лет [9]. Среди 80-летних больных годовая смертность была выше, чем у более молодых -OШ=4,92, 95% ДИ 2,32-10,46 (р<0,001) [15]. Более того, если госпитальная летальность с течением времени снижается в большинстве центров, то годовая и 5-летняя смертность меняются незначительно [8,11].…”
Section: Discussionunclassified